Determinants Theory of Planned Behavior on Student’s Interest in Using Financial Technology - Driana Leniwati; Pradio Rachmad Brilyan; Endang Dwi Wahyuni (Universitas Muhammadiyah Malang, 2021)
The purpose of this study was to determine the effect of factors in theory of planned behavior on the interest of using financial technology in University of Muhammadiyah Malang accounting students. The factors in this theory are attitude, subjective norm, and perceived control behavior. This study also reveals others factors that influence the interest of using financial technology. The method used in this study is a mixed method research. Quantitative data obtained from questionnaires, and qualitative data obtained from interviews with several students. Results of this study found a positive and significant influence on attitude and perceived behavorial control on the interest of using financial technology and there was no significant effect of subjective norm on the interest of using financial technology. Results of this study also found other factors that influence interest of using financial technology, including privacy, needs, and risks. these factors can be taken into consideration in developing financial technology in the future.